2014
DOI: 10.1007/s10549-014-3119-z
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-nicastrin monoclonal antibodies elicit pleiotropic anti-tumour pharmacological effects in invasive breast cancer cells

Abstract: The goal of targeted cancer therapies is to specifically block oncogenic signalling, thus maximising efficacy, while reducing side-effects to patients. The gamma-secretase (GS) complex is an attractive therapeutic target in haematological malignancies and solid tumours with major pharmaceutical activity to identify optimal inhibitors. Within GS, nicastrin (NCSTN) offers an opportunity for therapeutic intervention using blocking monoclonal antibodies (mAbs). Here we explore the role of anti-nicastrin monoclonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…Furthermore, Lombardo et al [6] reported that NCSTN regulates Akt activation in breast cancer cells and that NCSTN inhibition in malignant breast cells can inhibit breast tumour formation in vivo. Studies have also demonstrated that anti-NCSTN monoclonal antibodies exert antitumour effects in invasive breast cancer cells [8]. Notably, these results are consistent with not only the KEGG pathway results for GSEA based on TCGA data but also our observation that NCSTN depletion could induce apoptosis and reduce proliferation in HCC cell lines, partly through the PI3K/Akt pathway.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, Lombardo et al [6] reported that NCSTN regulates Akt activation in breast cancer cells and that NCSTN inhibition in malignant breast cells can inhibit breast tumour formation in vivo. Studies have also demonstrated that anti-NCSTN monoclonal antibodies exert antitumour effects in invasive breast cancer cells [8]. Notably, these results are consistent with not only the KEGG pathway results for GSEA based on TCGA data but also our observation that NCSTN depletion could induce apoptosis and reduce proliferation in HCC cell lines, partly through the PI3K/Akt pathway.…”
Section: Discussionsupporting
confidence: 91%
“…NCSTN, the largest constituent of the γ-secretase complex [24], has a single transmembrane domain and a large extracellular domain with functional regions [8]. Intriguingly, it has been reported that NCSTN could exert its function alone rather than participate in the γ-secretase complex in mouse muscle [25], which indicates that NCSTN is likely to exert some functions independently.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blocking of Jagged1 prevented and reversed lung goblet cell metaplasia in mouse models (and these effects were enhanced when Jagged2 was simultaneously inhibited), raising the provocative possibility that such treatments might be clinically deployed for respiratory disease characterized by excess mucus secretions (384). In addition to antibodies to receptors and ligands, antibodies to Nicastrin have been explored preclinically (190,263), although they, like GSIs, are likely to affect all ␥-secretase-cleaved proteins (244). Antibodies can also be used for GVHD, with few reported side effects (723; for review, see Ref.…”
Section: Therapeutics and Strategies For Targeting Notch Signalingmentioning
confidence: 99%
“…Haywashi and colleagues synthesized a monoclonal antibody against the extracellular domain of Nicastrin reporting the neutralisation of GS activity. We fully characterized two mAbs showing tumor reduction in vivo of triple negative breast cancer cell lines ( [16] and [17] ). In this paper, we highlight our recent study [18] on the efficacy of GSI PF03084014 and anti-Nicastrin mAbs to partially revert the EMT process and re-sensitize ETR breast cancer cells.…”
Section: Research Highlightmentioning
confidence: 99%